Optimalisasi Manajemen Barang Tenggat Waktu dan Lelang pada Penggadaian Yapusa - Kisma, Kisma Guruh Harta Putra (ProTekInfo(Pengembangan Riset dan Observasi Teknik Informatika), 2024)
Pegadaian Yapusa Bangil is a financial institution that provides pawn services to the public. Along with the development of technology and the demands of operational efficiency, the goods management and auction process at Pegadaian Yapusa is still carried out manually, which has the potential to cause errors, delays, and a lack of transparency. This research aims to design and develop an item management application that can control the entry and exit of goods and set deadlines for goods to be auctioned automatically. This application is designed to improve operational efficiency and reduce potential errors in managing goods at Pegadaian Yapusa. The main features of this app include accurate item recording and automatic notifications for items that are close to the deadline. The research methods used in development include interviews, observations, and literature studies to collect relevant data and information. The results of this study show that the application of goods management can help increase productivity and efficiency in the management of goods at Pegadaian Yapusa. In addition, this application also contributes to the development of theories and concepts in the fields of technology, business, and management. With this application, it is hoped that Pegadaian Yapusa can compete in the current digital era and provide better services to the community